Stability analysis of single-cross hybrids of maize (Zea mays L.) produced from selected and unselected inbred lines. - GAMA, E. E. G. e (1978)
Stability of yield performance is a desirable characteristic in maize (Zea mays L.) hybrids. Several methods have been proposed and used for measuring yield stability in applied studies. Recently Eberhart and Russel (1966) presented a method to compared hybrids for stability of performance over a series of environments. Inter-population Design II crosses intra-population diallel crosses were made using unselected lines from the two maize populations BSTE and PHPRC. The selected lines were chosen as superior on the basis of paired plant inter-population crosses tested from the SOxSO through S4xS4 generation. Six sets, each including 28 selected and 28 unselected crosses, were evaluated in simple lattice designs that were grown at three Iowa locations for threeyears. The conventional analyiss of variance combined over years and locations and the stability analyses of variance, which included mean yield, regression coeficient, and deviations from the regression, were computed for the selected and unselected, was more productive and stable over nine environments. The selected group of hybrids had significantly greater grain yield than the unselected hybrids. Significant genotype x environemnt interaction existed for the selected and unselected groups of hybrids, indicating that they differed in either rank or relative yield with environments.The selected and unselected groups of hybrids, therefore, had similar contributions to the total genotype x environment interaction variance. These two group of hybrids (...)